Insight into Biological Control Potential of Hirsutella citriformis against Asian Citrus Psyllid as a Vector of Citrus Huanglongbing Disease in America - Pérez González, Orquídea; Gómez Flores, Ricardo Alberto; Tamez Guerra, Patricia (Molecular Diversity Preservation International, 2022)
Studies on Hirsutella citriformis Speare are scarce. Among these, some reports have focused on phenotypic identification, based on its morphological structure and morphometric characteristics. This fungus is known to control economically important citrus crop pests. In recent years, H. citriformis has received increased attention as a control agent for the Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Liviidae), which causes the Huanglongbing (HLB) disease. Unfortunately, formal H. citriformis strains characterization is marginal, which mainly involves the role of biologically active exudates (metabolites) produced during their growth. Information regarding their mode of action and biocontrol potential is limited. However, epizootics reports of this fungus, under suitable environmental conditions for its development (25 °C to 28 °C and ~80% relative humidity), have demonstrated its parasitization efficacy. Therefore, it becomes challenging to determine whether H. citriformis strains may be developed as commercial products. In this review, we showed relevant information on isolation and bioassay strategies of H. citriformis to evaluate potential biocontrol strains under laboratory and field conditions in America.